Effect of MnCl2 Additive on Optical and Dispersion Parameters of Poly methyl Methacrylate Films - Nadir Fadhil Habubi (Journal of Global Pharma Technology, 2016)
PMMA films with various content of MnCl2 additive (1, 3%) are prepared by casting method. Amorphous films of PMMA-Mn are examined using X-ray diffraction (XRD). UV-Visible spectrophotometer is used to record the transmittance spectra, which decreased with the increasing of MnCl2. Energy gap value decreased from 3.91 eV for PMMA to 3.39 eV for film with 3% additive of MnCl2, while the Urbach energy are increased from 555 meV to 741 meV for the same additives. Dispersion parameters are determined using Wemple and DiDomenico model. The Ed, Eo, and So increased with the increasing of MnCl2 additive, while n (0), λo, and M-1, M-3 are decreased.Keywords: PMMA, Dispersion parameters, Composite, Optical properties.